Analisis Sistem Dropship Marketing Perspektif Konsep Maqashid Syariah Al-Syatibi - Soviana, Riqqa; Abidin, Zainal (TAWAZUN: Journal of Sharia Economic Law, 2020)
Dropship marketing system is a method of buying and selling online that is intended to achieve ease of transaction between seller and buyer. The benefit to be realized utilizes e-commerce as a practical modern tool. But in practice found a problem in this system that questions the element of mutual benefit between the seller and buyer. The problem is in the form of no need for a seller (dropshipper) to have merchandise to be traded. Whereas the existence of merchandise is a harmony and the conditions that must be met in the practice of buying and selling in order to avoid the element of uncertainty (gharar). Based on that problem then this research was made. This study aims to examine in depth the marketing implementation of the dropship system with the analysis of the concept of maqashid sharia al-Syatibi. The method used is in the form of a literature review with secondary supporting references. The results of this study indicate that the dropship marketing system that has been practiced by the wider community is not in accordance with the concept of maqashid syariah al-Syatibi. This is caused by the existence of lafadz clear orders and prohibitions related to the necessity of having merchandise by the seller, so that between the seller and buyer there is no party who feels disadvantaged. In connection with the most important thing, namely the fulfillment of the elements of maintenance of religion, soul, reason, honor and descent, as well as property as a condition for the achievement of sharia maqashid.